2016
DOI: 10.1186/s13690-016-0122-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of clinical manifestations of vitamin a deficiency among preschool children in asgede-tsimbla rural district, north Ethiopia, a community based cross sectional study

Abstract: BackgroundVitamin A Deficiency is a common form of micronutrient deficiency, globally affecting 33.3 % of preschool-age children. An estimated of 44.4 % of preschool children in Africa were at risk for vitamin A deficiency. In Ethiopia, vitamin A deficiency leads to 80,000 deaths a year and affects 61 % of preschool children. The aim of this study was to investigate the prevalence and associated factors with the night blindness, Bitot’s spot and vitamin A intake among preschool children in rural area, Asgede-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 9 publications
2
31
1
Order By: Relevance
“…High risk of selection bias was observed in eight studies. Measurement bias was observed in three studies [28,32,34]. Bias related to analysis was also observed in three studies [8,27,33] (Supplementary file 1: Table S1).…”
Section: Risk Of Bias and Heterogeneitymentioning
confidence: 84%
See 3 more Smart Citations
“…High risk of selection bias was observed in eight studies. Measurement bias was observed in three studies [28,32,34]. Bias related to analysis was also observed in three studies [8,27,33] (Supplementary file 1: Table S1).…”
Section: Risk Of Bias and Heterogeneitymentioning
confidence: 84%
“…The national prevalence of child night blindness was 0.8% in 2005 with high rate in the Harari region (1.1%) followed by the Amhara and Benishangul-Gumuz (both 1.0%) [14]. Likewise, about 1.2% of child night blindness was documented in the rural Tigray region in 2014 [32] and the lowest prevalence (0.6%) was reported in Amhara region in 2015 [33] ( Table 3). The overall prevalence of the meta-analysis of 13 studies, according to the Der Simonian-Laird random-effects model, revealed that the pooled prevalence of night blindness among preschool-age children in Ethiopia was 2.8% (95% CI: 1.9%-3.8%) ( Figure 7).…”
Section: Prevalence Of Clinical Vitamin a Deficiency (Xerophthalmia)mentioning
confidence: 95%
See 2 more Smart Citations
“…Open Access Library Journal pre-school children [3]. Vitamin A deficiency remains a widespread public health problem among women and children in the developing world [4], and it increases morbidity and mortality due to increased susceptibility to infection [5].…”
mentioning
confidence: 99%